2014
DOI: 10.1038/srep04862
|View full text |Cite
|
Sign up to set email alerts
|

Independent strong association of HLA-A*02:06 and HLA-B*44:03 with cold medicine-related Stevens-Johnson syndrome with severe mucosal involvement

Abstract: Stevens-Johnson syndrome (SJS) and its severe variant, toxic epidermal necrolysis (TEN), are acute inflammatory vesiculobullous reactions of the skin and mucous membranes. Cold medicines including non-steroidal anti-inflammatory drugs (NSAIDs) and multi-ingredient cold medications are reported to be important inciting drugs. We used two sample sets of Japanese patients to investigate the association between HLA genotypes and cold medicine-related SJS/TEN (CM-SJS/TEN), including acetaminophen-related SJS/TEN (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
147
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 90 publications
(151 citation statements)
references
References 28 publications
3
147
0
1
Order By: Relevance
“…9 We also documented that HLA-A*02:06 with TLR3 polymorphisms exerted more than additive effects 23 and that HLA-A*02:06 with PTGER3 polymorphisms exhibited additive effects in CM-SJS/TEN with SOC. 11 Although our sample numbers were small, we found that HLA-A*02:06 with Rec114 rs16957893 CG might also exert more than additive effects in CM-SJS/TEN with SOC (OR = 110, P = 4.45 × 10 − 8 ) (Supplementary Table 5).…”
Section: Resultsmentioning
confidence: 55%
See 3 more Smart Citations
“…9 We also documented that HLA-A*02:06 with TLR3 polymorphisms exerted more than additive effects 23 and that HLA-A*02:06 with PTGER3 polymorphisms exhibited additive effects in CM-SJS/TEN with SOC. 11 Although our sample numbers were small, we found that HLA-A*02:06 with Rec114 rs16957893 CG might also exert more than additive effects in CM-SJS/TEN with SOC (OR = 110, P = 4.45 × 10 − 8 ) (Supplementary Table 5).…”
Section: Resultsmentioning
confidence: 55%
“…This is consistent with findings reported in our earlier studies; they had shown a strong association between SJS/TEN with SOC and HLA-A*02:06. 8,9,[17][18][19] Outside of the HLA region, there were 82 polymorphisms manifesting associations with Po10 − 7 in the allele frequency model. Of these, four exhibited MAF40.05 and they were located on chromosome 16.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…HLA-B*5701, HLA-B*5801, HLA-B*1502, HLA-A*3101, HLA-A*0206, HLA-B*4403, HLA-A29, HLA-B12, HLA-DR7, and HLA-A2 are linked to SJS drug hypersensitivity reactions. [38][39][40][41] HLA-DQB1*0601, HLA-DQA1*0103, DQB1*0301, and HLA-A*0206 are linked to ocular manifestations in SJS. 42 Genetic influences can explain why SJS occurs in multiple family members even though it is a rare condition 43 or why it recurs in certain individuals.…”
Section: Genetic Predispositionmentioning
confidence: 99%